First-in-human study to assess the safety, pharmacokinetics and pharmacodynamics of BMS-986177/JNJ-70033093, a direct, reversible, small molecule Factor XIa inhibitor in healthy volunteers. (25th November 2020) - Perera, V; Wang, Z; Luettgen, J; Wang, J; Li, D; Desouza, M; Cerra, M; Seiffert, D
Abstract: Background: Inhibition of Factor XIa (FXIa) may provide a novel mechanism for systemic anticoagulation without increasing the risk of clinically significant bleeding in many conditions predisposing to a high risk of thrombotic or bleeding events. BMS-986177/JNJ-70033093 (BMS-177/JNJ-3093) is a small molecule that inhibits FXIa with high affinity and selectivity. Depending on the indication, BMS-177/JNJ-3093 may provide benefit to patients as add-on therapy to current standard of care (SOC) antithrombotic agents or potentially as a replacement for current SOC. Purpose: To assess the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of single and multiple oral doses of BMS-177/JNJ-3093 in healthy subjects. Methods: This was a 2-part, randomized, double-blind, placebo-controlled, sequential single- (Part A) and multiple- (Part B) ascending dose study to assess the safety, tolerability, PK, and PD of BMS-177/JNJ-3093 in healthy subjects. In Part A (SAD) of the study, 48 subjects were treated in 6 panels (8 subjects per panel). The 200 mg and 500 mg dose panels investigated the impact of a high fat diet on PK. In Part B (MAD), 56 subjects were treated in 7 panels (8 subjects per panel) on a once daily (QD) or twice daily (BID) regimen for a 14-day period. Within each panel in Parts A and B, subjects were randomized to receive either BMS-177/JNJ-3093 or matched placebo (3:1). Results: Administration of single ascending doses of BMS-177/JNJ-3093 up to 500 mg and multiple ascending doses of BMS-177/JNJ-3093 up to 200 mg BID or 500 mg QD for 14 days were safe and well tolerated. No subjects had a clinically significant bleeding event. All treatment-emergent adverse events were mild in severity. After single doses of BMS-177/JNJ-3093 ranging from 4 to 500 mg in fasted status, BMS-177/JNJ-3093 plasma concentration reached Cmax at 3 h postdose in all panels, indicating a similar rate of absorption. The terminal half-life ranged from 8.26 to 13.8 h across SAD panels. Over 20 to 200 mg, a dose proportional increase was observed; however, saturable absorption was seen at higher doses of 300 and 500 mg. Food also increased the bioavailability of BMS-177/JNJ-3093. In the MAD portion of the study, based on visual inspection of trough plasma concentration profiles, BMS-177/JNJ-3093 plasma concentration steady state was reached between 1–3 dosing days (ie, Days 2–4) for the QD panels and 6 dosing days (ie, Day 7) for the 200 mg BID panel. Renal excretion was relatively low, ranging from 8–20%. After single oral dose or multiple oral doses, there is a clear trend that aPTT was prolonged and the magnitude of change was related to drug exposure. Conclusion: BMS-177/JNJ-3093 was safe and well tolerated in healthy volunteers. The PK and PD profile demonstrates suitable dosing properties for further clinical studies. Currently, two Phase II studies are ongoing. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): This work was sponsored by Bristol-Myers Squibb and Janssen Research & Development, LLC